The Circumstances of Things and Persons that Can Allow a Case for Nullity of Marriage (Mitis Iudex - "The way of proceeding...," Art. 14) - Adamowicz, Leszek (Iustitia, 2015)
The author is discussing issues concerning the new provisions regarding the new process for declaring the nullity of a marriage i.e., shortened process. The Bishop's (shortened) process presumes certain prerequisites: compatible arguments of the parties, "strong" evidence for nullity provided in the initial stage, and a description of the circumstances that led to the decision to end the marriage. The author critically analyses art. 14 §1 of "The way of proceeding in cases regarding the declaration of the nullity of a marriage." The cited criteria relate to suspected defects of consent, such as simulation fraud, lack of use of reason, grave lack of due discretion concerning the essential rights and obligations of marriage, and a psychological incapacity to assume these obligations.